2008
DOI: 10.1038/sj.bjc.6604683
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study and meta-analysis of SULT1A1 Arg213His polymorphism for gene, ethnicity and environment interaction for cancer risk

Abstract: Cytosolic sulphotransferase SULT1A1 plays a dual role in the activation of some carcinogens and inactivation of others. A functional polymorphism leading to Arg 213 His substitution (SULT1A1*2) affects its catalytic activity and thermostability. To study the association of SULT1A1*2 polymorphism with tobacco-related cancers (TRCs), a case -control study comprising 132 patients with multiple primary neoplasm (MPN) involving TRC and 198 cancer-free controls was carried out. One hundred and thirteen MPN patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 67 publications
2
27
0
Order By: Relevance
“…Contradicting association studies have also been published for prostate cancer [31][32][33]. A recent meta-analysis concluded that the SULT1A1*2 polymorphism was protective in genitourinary cancers, but was associated with increased upper aerodigestive tract cancers [34].…”
Section: Important Variantsmentioning
confidence: 99%
“…Contradicting association studies have also been published for prostate cancer [31][32][33]. A recent meta-analysis concluded that the SULT1A1*2 polymorphism was protective in genitourinary cancers, but was associated with increased upper aerodigestive tract cancers [34].…”
Section: Important Variantsmentioning
confidence: 99%
“…We noted that the divergent genetic background and differing carcinogen exposure in various populations may explain the differing risk assessments related to the genetic polymorphisms [20][21][22]. Our study is weakened somewhat by recall bias, in that it can be difficult to recall carcinogen exposure at time points in the past, and cases are more motivated than controls to recollect past exposures.…”
Section: Discussionmentioning
confidence: 75%
“…Given the ethnic differences in the impact of SULT1A1 Arg 213 His polymorphism reported in BC risks among women from different populations [13,14,16,17], further studies are needed to better define the role of SULT1A1 Arg 213 His polymorphism in MBC risk in additional populations.…”
Section: Discussionmentioning
confidence: 99%
“…Within the context, SULT1A1 catalyzes the sulfonation of estrogens to form biologically inactive estrogen sulfates, thus reducing the level of estrogens' exposure in target tissues, such as mammary tissue. The SULT1A1 Arg 213 His variant (rs9282861), is a very common functional polymorphism of the SULT1A1 gene [7] and many studies have associated it with BC in women, though with contrasting results [8][9][10][11][12][13] Recent meta-analysis studies have shown that SULT1A1 Arg 213 His variant is associated with increased risk of BC, particularly in post-menopausal women [14][15][16][17][18]. SULT1A1 Arg 213 His variant (rs9282861) consists of a G to A transition at nucleotide 638 and causes an Arginine (Arg) to Histidine (His) substitution at aminoacid 213.…”
Section: Introductionmentioning
confidence: 99%